Pelatihan Pembuatan Sabun Padat Herbal di Desa Cileles Kabupaten Tangerang - Diana Sylvia; Dina Pratiwi (Jurnal Ilmiah Pangabdhi, 2021)
Cooking oil is one of the main staples needed in households. Cooking oil that is no longer used can cause household waste. Unused waste oil or used cooking oil, if not managed properly, will cause environmental pollution. There are still many people who do not know how to process the remaining unused oil. Therefore, as a form of community service from the Tangerang Muhammadiyah College of Pharmacy, we tried to invite the community in the Green Palme Housing, Cileles, Tangerang Regency to be able to participate in processing used cooking oil waste so that it can be used as a useful product, namely soap making. The method used in this activity is to provide training on recycling used cooking oil by adding lemongrass essential oil to make herbal-based bath soap. Community service broadly includes 3 activities, namely data collection of participants, delivery of material by lecturers, and mentoring of soap making practices by lecturers of STF Muhammadiyah Tangerang. This training activity is expected to open up opportunities for entrepreneurship, encourage industrial houses, assist in packaging and product marketing to the community, to improve the living standards of the communities around those affected by PPKM, create jobs, and make people's lives better.